Pengembangan Kawasan Objek Wisata Di Desa Buluhcina Dengan Pendekatan Arsitektur Neo-Vernakular - Cipta Ariyadi; Wahyu Hidayat; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The development of a tourist attraction area in the village of Buluhcina is an effort to redevelop the tourism object of the Buluhcina Village. Neo-Vernacular approach was chosen as the theme of this design because Neo-Vernacular is a stream that embraces modernism without theleave of existing traditional elements, this is in accordance with the design concept that prioritizes local culture and still incorporates elements of modernization. The basic concept of thearrangement of the tourism object area of Buluhcina Village was taken from